DIVORCE CAUSED BY HYPERSEXUAL PSYCHOLOGICAL DISORDERS IN HUSBAND - KUSMAYANTI, HAZAR (Nurani, 2019)
The family itself was initially formed through a marriage between a man and a woman who was considered feasible. One of the purposes of marriage is the fulfillment of the biological needs, yet this biological needs fulfillment can be a problem when one party is suffering from hypersex. In the case of divorce numbered 350/PDT. G/2014/PA.JB. that happened in Religion of West Jakarta Court, the wife as the Plaintiff felt it was not capable of serving the biological desire of her husband that ultimately give rise to conflict in their marriage life. the case is decided in verstek by the judge because the defendant i.e., husband of the plaintiff is not present in the trial even though it was called officially and worth. Based on the results of the research, the psychological disorders hypesex as the reason for the divorce is not set explicitly in the Act of marriage, Islamic Law Compilation, nor the Goverment Rules No. 9 Year 1975. However, in this case the judge considers that the hypersex psychological disorders lead to continuous conflict and the conflict resulted in the defendant leave plaintiff. Consideration of the judge in the court decision that has complied with the provisions concerning the grounds for divorce are set forth in article 19 Government Regulation No. 9 years 1975 and section 116 Islamic Law Compilation, so that the judge has the right judges grant a divorce lawsuit plaintiff filed. In addition the verdict which decided in verstek by the judge had in accordance with existing procedures and his lawsuit is not against the rights so that is in compliance with existing provisions in article 125 of HIR. Keywords: Divorce, Hypersexual, Verstek